A Strategy to Analyze the Metal Packaging Market in the Food Cans Industry Using Agent-Based Simulation - Chaverra Vargas, Luis F.; Marmolejo Saucedo, José Antonio (Springer, 2024)
Companies that manufacture metal packaging for canned jalapeño peppers require forecasts to determine the amounts of inventory needed to meet customer demand and anticipate sales opportunities. The nature of jalapeño pepper production depends on factors such as planting, harvesting, seasonality, pests, and climate change, among others, which generate a lot of uncertainty when estimating the needs of the client. The purpose of this research is to solve the problem of having a simple and more accurate forecast of jalapeño pepper availability in the market for the metal packaging business. Forecasts are currently based on historical data; the adjustment of these predictions does not always follow sudden changes in the data, and for this reason, there are other more complex methods, which use mathematics, where it seems that a mathematical expert is needed more than an expert in the business where the forecasting tool is used. Agent-based simulation allows the development of interaction rules between the different market agents, which, in a dynamic and flexible way, allows the development of simple models with complex behaviors where there are no formulas that govern them and allow interaction between them. The ABS model provides more details about the behavior of the jalapeño pepper crop, compared to the models evaluated in this chapter, which are based on equations.
Keywords: SEMARNAT (Secretaría de Medio Ambiente y Recursos Naturales); INEGI (Instituto Nacional de Estadística y Geografía); ABS (Agent-Based Simulation)